the vertical asymptote is x = -4 (option 2)
Step-by-step explanation:
![f(x)\text{ =}(x-3)/(x+4)](https://img.qammunity.org/2023/formulas/mathematics/high-school/cowpsr4serto51p94un6ughm8vxumc68jj.png)
The vertcal asymptote of a function, is the value of x when the denominator is equated to zero:
![\begin{gathered} \text{Denominator = x + 4} \\ \text{equating to zero:} \\ x\text{ + 4 = 0} \\ \text{subtract 4 from both sides:} \\ x\text{ +4 -4 = 0 - 4} \\ x\text{ = -4} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/44i4fvdnt8vbhxi787vfm0v2esp9wrkyuu.png)
The x - intercept is the value of x when f(x) = 0
![\begin{gathered} f(x)\text{ =}(x-3)/(x+4) \\ 0\text{ = =}(x-3)/(x+4) \\ 0(x\text{ + 4) = x - 3} \\ 0\text{ = x - 3} \\ x\text{ = 3} \\ x-\text{intercept: }(3,\text{ 0)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/6cvzou1wx9jch5t5c9za0xeorfk8ozr9h2.png)
The y-intercept is the value of f(x) when x = 0
![\begin{gathered} f(x)\text{ = }(x-3)/(x+4) \\ f(x)\text{ =}(0-3)/(0+4) \\ f(x)\text{ = }=\text{ }(-3)/(4) \\ y-\text{intercept = (0, -3/4)} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/high-school/o7tgmv843ilb6b7hn5w1ygmz1p9e3529cr.png)
Comparing the results we got and the options, the only option that has same answer as our calculation is the vertical asymptote is x = -4 (option 2)